Metformin, a biological and synthetic overview. (15th April 2023) - Hernández-Velázquez, Edson D.; Alba-Betancourt, Clara; Alonso-Castro, Ángel J.; Ortiz-Alvarado, Rafael; López, Jesús A.; Meza-Carmen, Victor; Solorio-Alvarado, César R.
Graphical abstract: Abstract: Metformin is the most widely known anti-hyperglycemic, officially acquired by the USA government in 1995 and in 2001 it became the most prescribed treatment for type II diabetes. But how did it become the must-use drug for this disease in such a short period of time? it all started with traditional medicine, by using a plant known as "goat's rue" for the reduction of blood glucose levels. Its use arose in 1918 and evolved to the metformin synthesis in laboratories a couple of years later, using very rudimentary methods which involved melting and strong heating. Thus, a first synthetic route that allowed the preparation of the initial metformin derivates was established. Some of these resulted toxics, and others outperformed the metformin, reducing the blood glucose levels in such efficient way. Nevertheless, the risk and documented cases of lactic acidosis increased with metformin derivatives like buformin and phenformin. Recently, metformin has been widely studied, and it has been associated and tested in the treatment of type II diabetes, cancer, polycystic ovarian syndrome, cell differentiation to oligodendrocytes, reduction of oxidative stress in cells, weight reduction, as anti-inflammatory and even in the recent COVID-19 disease. Herein we briefly review and analyze the history, synthesis, and biological applications of metformin and its derivates.